ESTIMASI POTENSI GENETIK SAPI PERAH FRIESIAN HOLSTEIN DI TAURUS DAIRY FARM, CICURUG, SUKABUMI - Hera Prahanisa; Sumadi (Sumadi); Adiarto (Adiarto) (Buletin Peternakan, 2011)
The objective of this study was to estimate potential genetic of Friesian Holstein at Taurus Dairy Farm, Cicurug, Sukabumi. Data observed were secondary data of milk yield, calving interval, service per conception, age at first calving, and length of lactation records of cows that have been experiencing one or more lactation since year 2003 to 2009, then were standardized based on milk yield by using correction factor 305 days of lactation period and mature equivalent (ME). Production trait (milk yield), reproduction traits (CI, S/C, length of lactation, and age at first calving) were analyzed by descriptive statistic. Data were analyzed by paternal half-sib correlation and nested method to get heritability, while the repeatability value were obtained by interclass and intraclass correlation method. Heritability and repeatability value then was used to count most probable producing ability (MPPA) and estimated real producing ability value and estimated transmitting ability (ETA) and breeding value (NP) of dairy cows. Estimates of heritability of milk yield by using nested are 0.287±0.135 (h2s), 0.310±0.154 (h2d), and 0.299±0.103 (h2(d+s)), and paternal half-sib correlation method was 0.63±0.23. Estimates of CI heritability with paternal half-sib method was 0.46±0.23, and values obtained using nested were 0.038±0.106 (h2s), 0.733±0.231 (h2d), 0.385±0.117 (h2(d+s)). Estimated heritability of S/Cwith paternal half-sib method was 0.001±0.110 and using nested method are -0.022±0.043 (h2s), 0.098±0.133 (h2d), 0.038±0.072 (h2(d+s)). Estimated value of milk yield repeatability with interclass correlation was 0.43±0.1 and intraclass correlation was 0.15±0.05. CI repeatability value with interclass correlation method was 0.00±0.09 and intraclass correlation was 0.19±0.07. S/C repeatability value with interclass correlation method was 0.12±0.15 and intraclass correlation was 0.02±0.05. Based on the calculation, the highest five ranks on the estimated relative value of MPPA and ERPA from 147 holstein friesian dairy cows with interclass repeatability method and 279 Friesian Holsteindairycows with intraclass method were 1966, 1941, 2180, 2087, and 2248. Database, Kimball, Beam, Doeboy, Paul, Varlour and Cassela get the highest rank, based on the estimated value of ETA and NP for 40 bulls using paternal half-sib heritability method and 38 bulls using nested heritability method.(Keywords: Friesian Holstein dairy cows, Milk yield, Reproduction traits, Genetic parameter)